Pengaruh Parental Belief terhadap Curiosity Anak Usia Sekolah Dasar pada Masyarakat Betawi - Rr. Zabrina I.B. Sulistyanti; Sri Hartati R Suradijono (Provitae: Jurnal Psikologi Pendidikan, 2019)
Curiosity in Indonesian children is considered lacking, indicated by their reluc-tance to ask question and low critical thinking skill. One factor which is often as-sociated with children’s curiosity development is their relationship with authority figure. This study aims to gain information about which aspect of parental belief that is seen as more important (especially related to autonomy and conformity), and how it affects children’s curiosity. This study involved 32 pairs of parent and child from Betawi society, as parental belief and curiosity are influenced by culture and Betawi society was deemed as the prototype of Indonesian society in the future. Parental belief was analyzed using repeated-measures ANOVA and Bonferroni while curiosity was analyzed using multiple regression. Results shows that Betawi parents in general believe that autonomy is as important as conformity (p = 0,897 >0,05 with problem solving skills, p = 1,000 >0,05 with practical skills, and p = 0,261 >0,05 in academic objectives aspect), except in socialization at school con-text (p = 0,008 <0,05), and parental belief has no significant effect on children’s curiosity (p values are in range 0,284-0,982 >0,05).